Taxing Land Rent in an Open Economy - Alberto Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper analyzes the effects of a land rent tax on capital formation and foreign investment in a life-cycle small open economy with endogenous labor-leisure choices. Differently from the previous literature, the consequences of land taxation critically depend on how the tax proceeds are used by the government. A land tax depresses capital formation, crowds out foreign investment and pulls up national wealth and consumption when consumers are lump-sum compensated for the tax. If the proceeds from taxation were used for financing un-productive government expenditure, land taxation would be neutral in its effects on capital stock, nonhuman wealth and labor. When the tax proceeds are used to reduce labor taxes, the land tax exerts ambiguous effects on capital stock and manhours, and spurs nonhuman wealth accumulation.
Keywords: E21; E62; H22; 330; Land Taxation; Labor Supply; Capital Accumulation; Overlapping-generations; Grundsteuer; Investition; Auslandsinvestition; Kleine offene Volkswirtschaft; Overlapping Generations; Theorie